BİSHOP ÇATISINA GÖRE KÜRESEL GÖSTERGELER ÜZERİNE - GÜLNAROĞLU, SERHAT (Fırat Üniveristesi, 2024)
3 boyutlu Öklid uzayında regüler eğriler üzerine birçok çalışma yapılmıştır. Birçok araştırmacı bu teoride Frenet çatı ve Bishop çatı gibi çatıları çalışmıştır. Bu çatılar eğriler ile ilgili karakterizasyonlarda bize yardımcı olur. Bu çalışmada, 3-boyutlu Öklid uzayında bishop çatıya göre küresel göstergeler incelenmiştir. Bunun için önce Öklid uzayında tip 2 bishop çatı verilmiş ve bunlar için yeni karakterizasyonlar elde edilmiştir.

Many studies have been done according to different frames of the theory of curves in Euclidean Space. Many researchers have studied frames such as the Frenet frame, Bishop frame in this theory. These frames help us in the characterization of curves. This study analyzes spherical indicatrix according to the bishop frame in Euclidean space. For this, firstly, the Type-2 Bishop frame is given in euclidean. Then new characterizations are obtained.
On spherical indicatrix according to bishop frame
Keywords: Matematik